Lifestyles and Quality of Life of Post Menopausal Women [Síntomas Climatéricos y Calidad de Vida de Usuarias de Consultorios de Atención Primaria de Salud, Santiago] - Lopez-Alegria, F (2011)
Background: During menopause the quality of life of women can be seriously deteriorated and influenced by lifestyles. Aim: To assess the prevalence of menopausal symptoms and their relationship with lifestyles and quality of life. Material and Methods: The Menopause Rating Scale (MRS), a survey that measures menopausal symptoms and has questions related to lifestyles, was applied to 1023 women aged 54 ± 6 years (range 45 to 64 years), consulting in primary health care clinics. A multiple linear regression analysis was used to evaluate the association between menopausal symptoms and lifestyle. Results: Fifty six percent of women did not have a paid work, 64% were nonsmokers and 90% did not perform any physical exercise. The most frequent menopausal symptoms referred were muscle and joint ailments (85%) followed by mental and physical exhaustion (80%). Sedentary women, smokers or those who did not to have time for leisure activities showed worst quality of life scores. Conclusions: Postmenopausal women with unhealthy lifestyles had the lower quality of life scores and more menopausal symptoms.